New Proposal for the Location of Ancient Turanu (URU tu-ra-nu) - Baaklini, Adonice-Ackad (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2018)
The city Turanu (URU tu-ra-nu) is one of the cities conquered by Tiglath-pileser III during his repression of the rebellion led by Azriau (king of Hamath?) in the northern part of Hamath and some northern Phoenician states in 738 BCE (RINAP 1: Tiglath-pileser III, 43, ii 16-24; the city is quoted l. 23). Based on the geographical context and the phonological rapprochement, Turmanin (scientific transcription from arabic: turmānīn) was proposed as a candidate for locating the ancient city (Lipinski 2000: 296; quoted also in Bagg 2007: 262).